Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Storage timescales and the crystal growth history recorded in the layered reservoir of the Unit 3 Kulanaokuaiki Tephra Member of the Uēkahuna Ash from Kīlauea volcano - Abigail R. Nalesnik; Kendra J. Lynn; Timothy R. Rose; Jessica M. Warren; Dawn C. S. Ruth; Kuan-Yu Lin; Donald A. Swanson (Contributions to Mineralogy and Petrology, 2026)
The Kulanaokuaiki Tephra Unit 3 (900 C.E.) was a subplinian basaltic scoria eruption, the largest known to have occurred at Kīlauea’s summit. The initiation mechanism and cause(s) of this highly hazardous eruption remain poorly understood, particularly as this style of activity has not been observed in the modern period. We use olivine diffusion timescales from Fe-Mg and lithium zoning to assess magma storage timescales and evaluate evidence for mixing prior to eruption. Of the 200 crystals assessed, 55% are normally zoned for forsterite and 45% are non-zoned. Zoned crystals (> 1 mm) ( n = 96) have average compositions of Fo 89 cores and Fo 81 rims, while small crystals 0.5–1 mm ( n = 14) have Fo 85 cores and Fo 82 rims. Modeled Fo diffusion timescales range from n = 17), reflecting growth processes and precluding their use for diffusion studies. Overall, our Unit 3 olivine dataset displays no evidence of magmatic priming shortly prior to eruption, unlike prior observations for the basaltic subplinian eruption of the Keanakāko‘i Tephra Unit E (1650 C.E.). Thus, explosive eruption magmas may be stored for considerably longer than previously thought, and magmatic priming is not a necessary precursor for Kīlauea’s explosive eruptions. We hypothesize that gas-driven filter pressing from crystallization of microlites and macrocrysts in the reservoir slurry contributed to the explosivity of the Unit 3 eruption.

A Numerical Study of Eastern Oyster (Crassostrea virginica) Larval Growth and Dispersal in Barataria Estuary, Louisiana, USA - Zhengchen Zang; Z. George Xue; Shaye E. Sable; Megan K. La Peyre; Kenneth A. Rose; Timothy A. Stephens; Brady Carter; David C. Lindquist; Yanda Ou; Ziyan Lei (Estuaries and Coasts, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Anatomy of Eurotamandua joresi (Mammalia) from Grube Messel, Germany, based on computed tomography, and implications for its relationships. Part I: Background and forelimb - Kenneth D. Rose; Renate Rabenstein; Jörg Habersetzer; Timothy J. Gaudin (Palaeobiodiversity and Palaeoenvironments, 2026)
Micro-computed tomography of the unique skeleton of Eurotamandua joresi Storch, 1981 (middle Eocene, Grube Messel)—initially described as the oldest myrmecophagid and the only known Old World xenarthran—reveals details of its skeletal anatomy that were previously obscured, enabling close comparative study for the first time. In this report we focus on the forelimb. The segmentation of scapula, humerus, radius, ulna, carpals, metacarpals and phalanges reveals exceptional specializations for scratch digging. These include numerous features that are strikingly similar to those of palaeanodonts, and to a lesser degree manids, but which contrast sharply with those of the xenarthrans Tamandua and Dasypus . Other features once thought to ally Eurotamandua with xenarthrans, such as a secondary scapular spine, absence of teeth, and a tubular snout, are not restricted to Xenarthra. The new forelimb characters are here incorporated into a phylogenetic analysis that includes xenarthrans, pholidotans, and palaeanodonts. This new analysis provides compelling evidence that Eurotamandua is related to Palaeanodonta (Laurasiatheria: Pholidotamorpha) rather than to Xenarthra, thus separating it from xenarthrans at the superordinal level. Consequently, there is no evidence that Xenarthra ever reached the Old World.

The lights are still on: the persistence and extraordinary density of the European lightbulb sea squirt Clavelina lepadiformis (Ascidiacea) in the Northwest Atlantic Ocean - Aria S. Lupo; Krystal Rose; Caleb Rose; Timothy J. Pusack; James T. Carlton (Biological Invasions, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Agronomic phosphorus fertiliser value of animal manures is comparable to monoammonium phosphate for wheat production - Maryam Barati; Timothy I. McLaren; Chelsea Janke; Simon Diffey; Michael J. Reading; Abraham Gibson; Terry J. Rose (Agriculture, Ecosystems & Environment, 2026)

In situ deformation of antigorite-olivine two-phase mixtures: Implications for dynamics and seismic anisotropy in the mantle wedge - Rose Hurlow; Wenhao Su; Wen-Yi Zhou; Feng Lin; Lowell Miyagi; Timothy Officer; Tony Yu; Yanbin Wang; Meiqian Wu; Qin Wang; Jin S. Zhang (Earth and Planetary Science Letters, 2025)

Evidence for mineral stratification in a zoned basaltic magma body at Kīlauea Volcano, Hawai’i: insights from the Kulanaokuaiki-3 tephra (≥ 1.0 ka) - Stephen J. Lynton; Timothy R. Rose (Contributions to Mineralogy and Petrology, 2025)

Housing insecurity, financial hardship and mental health - Timothy Ludlow; Jonas Fooken; Christiern Rose; Kam Ki Tang (Economics & Human Biology, 2025)

Benthic foraminiferal Mg/Ca response across the Aptian-Albian Boundary Interval at DSDP Site 511 (Falkland Plateau) - Barbara Balestra; Brian Huber; Jonathan Chen; Gabriela A. Farfan; Kenneth G. MacLeod; Timothy Rose; Adina Paytan; Timothy Gooding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Spatial modelling of present and future groundwater potentials in Nigeria; towards a sustainable water demand and supply - Esther Shupel Ibrahim; Joseph Timothy Chiroma; Musa Akin Abubakar; Samuel Achonu Ojih; Edmond Sunabiji Waziri; Rose Edwin Daffi; Ezekiel Yenne (Sustainable Water Resources Management, 2024)
The development of water resources in Nigeria has not risen alongside population increase. Although groundwater is the available source of water at all locations in Nigeria, groundwater aquifer is becoming deeper due to increased groundwater harvest, especially in urban areas. There is a need for continuous groundwater modelling using geological, climatic, environmental data, and spatial tools especially under climate change and intense landcover conversions. The Spatial Multi-Criteria Analysis (SMCA) was adopted in this study to model the current groundwater potential in Nigeria. The multi-criteria analysis tool in ArcGIS was explored to overlay the nine factor maps to model historic and futuristic groundwater potentials. Our groundwater factor maps show an interesting pattern across Nigeria, the southern parts show more potential considering suitability factors like; surface water density, rainfall, temperature, soil, land cover and elevation in the region. Whereas the upland regions even with higher rainfall and lower temperatures suitable for groundwater recharge, are disadvantaged by geomorphological factors. Northern part of Nigeria shows high potentials, considering the geology, soil, lineament density and slope, but disadvantaged by other factors like lower rainfall and higher temperatures. This informed the final groundwater potential maps; results for the historic potential revealed that, no location in Nigeria has optimal (9–10), very poor or no (1–2) groundwater potential. The results further revealed that areas with higher groundwater potentials are largely within the corridors of major rivers in Nigeria (Niger and Benue), covering about 17.6% of the Nigerian landmass, while 2.6%, 33.7, 44% and 2.2% are occupy areas with very low, low, moderate and very high groundwater potentials respectively. Further analysis highlighs locations of concern due to climatic and environmental changes. Interestingly, our groundwater projection results show a persistent increase in groundwater potential from 2021 to 2100 if current landuses and environmental factors are maintained, and if the projected increase in rainfall is true. Despite these groundwater potentials, the recent issues of shallow aquifers have been cautioned by scientists, especially due to groundwater uncertainties in Nigeria especially with intense landcover conversions, combined with accelerated water demands due to increase in population, and incessant groundwater extractions. Therefore, there is a need to seek caution in the pattern of unregulated and incessant groundwater harvest in Nigeria and we recommend frequent updates of the groundwater potential using geospatial tools to inform governing policies on a centralised consolidated sustainable water supply in Nigeria.

Farmer perspectives on desired catfish attributes in aquaculture systems in Nigeria. An exploratory focus group study - Timothy Manyise; Rose K. Basiita; Catherine M. Mwema; Olutokunbo Oyesola; Sunil Siriwardena; Bernadette Fregene; Steven M. Cole; Eric B. Dompreh; Rodolfo Dam Lam; Denise L. Lozano; Cristiano M. Rossignoli; John A.H. Benzie (Aquaculture, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

Rights based approaches to forest landscape restoration; learning from the Indian forest policy experience - Dhanapal Govindarajulu; Rose Pritchard; Ashwini Chhatre; Timothy Foster; Johan A. Oldekop (Forest Policy and Economics, 2023)

Justice and ethics in conservation remote sensing: Current discourses and research needs - Natalie D.L. York; Rose Pritchard; Laura Aileen Sauls; Charis Enns; Timothy Foster (Biological Conservation, 2023)

A New Preparation Method for 3D Bio-composite Filament Manufacturing: a Study on the Effects of Ball Milling on the Cohesion/Adhesion of an Agave tequilana Bagasse/PLA Pellet Mixture - Mathias Salignon; Simon Gray; Timothy Rose; Adriana Encinas-Oropesa (Circular Economy and Sustainability, 2023)
This study created a composite polymer for 3D printing from agave by-product using mechanical alloying process. The cold milling technique used by the ball mill is a standard procedure to homogenize metallic mixtures. This paper reports results from a series of laboratory tests to create a homogeneous mixture that could be extruded into a printable filament mixture of agave bagasse fibres and PLA pellets by using the kinetic energy of a ball mill. PLA and agave bagasse mixtures in this study were ground several times using this principle; steel and ceramic balls were used to grind them. The results of the study showed that this principle can be effective on a polymer-based mixture; indeed, an adhesion between the pellets and the agave bagasse fibres was obtained. The results showed the different parameters that influence the mixture quality as the milling time, the ball material, the number of balls, the mixture concentration and the rotational speed. Optical and ESEM/EDX analyses have confirmed our expectations about cohesion between fibres pulverized in powder and pellet adhesion, where powder accumulation on all the surfaces was detected. The absence of powder penetration in the pellets allowed us to explain the losses obtained during the process and to find new solutions to reduce them. Proof-of-concept parts were 3D printed with agave bagasse/PLA filaments. Their printed quality can be compared to that of commercial filaments. These results offer new perspectives to reuse agricultural by-products to create composite filament with a chemical-free manufacturing process.

Burning trees in frozen soil: Simulating fire, vegetation, soil, and hydrology in the boreal forests of Alaska - Melissa S. Lucash; Adrienne M. Marshall; Shelby A. Weiss; John W. McNabb; Dmitry J. Nicolsky; Gerald N. Flerchinger; Timothy E. Link; Jason G. Vogel; Robert M. Scheller; Rose Z. Abramoff; Vladimir E. Romanovsky (Ecological Modelling, 2023)

Harnessing the structural attributes of NiMg-CUK-1 MOF for the dual-function capture and transformation of carbon dioxide into methane - Timothy Zurrer; Emma Lovell; Zhaojun Han; Kang Liang; Jason Scott; Rose Amal (Chemical Engineering Journal, 2023)

Identifying transformational space for transdisciplinarity: using art to access the hidden third - Toddi A. Steelman; Evan Andrews; Sarah Baines; Lalita Bharadwaj; Emilie Rose Bjornson; Lori Bradford; Kendrick Cardinal; Gary Carriere; Jennifer Fresque-Baxter; Timothy D. Jardine; Ingrid MacColl; Stuart Macmillan; et al. (Sustainability Science, 2019)

Telemedicine Delivery and Successful Reimbursement in Toxicology - Peter W. Crane; Timothy J. Wiegand; Michael Kamali; Marilynn Reif; Rose Wratni; Ronald Montante; Tracey Loveland (Journal of Medical Toxicology, 2018)

Multiple abiotic factors correlate with parallel evolution in Australian soil burrowing cockroaches - Perry G. Beasley‐Hall; Timothy R. C. Lee; Harley A. Rose; Nathan Lo (Journal of Biogeography, 2018)
Aim The ways in which abiotic factors contribute to parallel evolution—the evolution of similar, derived phenotypes in independent, closely related lineages—remain understudied. Australian cockroaches of the subfamilies Panesthiinae (“wood feeders”) and Geoscapheinae (“soil burrowers”) are two closely related groups that provide a striking example of parallel evolution of burrowing behaviour. The ancestral wood‐feeding panesthiines migrated from Asia ~20 million years ago before soil burrowing was independently acquired multiple times in the derived geoscapheines. Here, we investigate whether specific abiotic factors were associated with the parallel evolution of soil burrowing behaviour, and whether divergence events of geoscapheines from panesthiine ancestors are consistent with niche conservatism or divergence. Location The Australian mainland, including the areas in which selected Australian Panesthiinae and Geoscapheinae cockroach species are distributed. Methods We generated environmental niche models for members of the Australian Geoscapheinae and Panesthiinae using presence‐only data and abiotic variables related to temperature, precipitation, and soil composition from BioClim and the Australian Soil Resource Information System. We used an existing phylogenetic framework to compare environmental niche models and tested for niche conservatism versus divergence. Morphological convergence was assessed by a regression analysis and principal components analysis of leg segment and body dimensions in soil burrowers and wood feeders. Results We found no relationship between niche similarity and time since divergence, and only limited evidence for phylogenetic signal with respect to the environmental variables examined. We found that soil burrowing behaviour is consistently correlated with thirteen abiotic factors associated with aridity, including a wider range of temperatures and lower precipitation levels. Evidence for convergence in leg morphology and body dimensions across soil burrowers was found. Main conclusions Our results are consistent with soil burrowing behaviour evolving in response to ancient aridification events following the arrival of the Panesthiinae in Australia. Our results suggest a scenario of niche divergence between soil burrowers and each of their wood feeding sister taxa. There is evidence for morphological convergence on a “shovel‐like” protibiotarsus in the Geoscapheinae that would aid in burrowing into soil.

Corrigendum: Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Rose M. Cory; Timothy W. Davis; Gregory J. Dick; Tom Johengen; Vincent J. Denef; Michelle Berry; Sarah E. Page; Susan B. Watson; Kate Yuhas; George W. Kling (Frontiers in Marine Science, 2017)

Cyanobacterial harmful algal blooms are a biological disturbance to Western Lake Erie bacterial communities - Michelle A. Berry; Timothy W. Davis; Rose M. Cory; Melissa B. Duhaime; Thomas H. Johengen; George W. Kling; John A. Marino; Paul A. Den Uyl; Duane Gossiaux; Gregory J. Dick; Vincent J. Denef (Environmental Microbiology, 2017)
Summary Human activities are causing a global proliferation of cyanobacterial harmful algal blooms (CHABs), yet we have limited understanding of how these events affect freshwater bacterial communities. Using weekly data from western Lake Erie in 2014, we investigated how the cyanobacterial community varied over space and time, and whether the bloom affected non‐cyanobacterial (nc‐bacterial) diversity and composition. Cyanobacterial community composition fluctuated dynamically during the bloom, but was dominated by Microcystis and Synechococcus OTUs. The bloom's progression revealed potential impacts to nc‐bacterial diversity. Nc‐bacterial evenness displayed linear, unimodal, or no response to algal pigment levels, depending on the taxonomic group. In addition, the bloom coincided with a large shift in nc‐bacterial community composition. These shifts could be partitioned into components predicted by pH, chlorophyll a , temperature, and water mass movements. Actinobacteria OTUs showed particularly strong correlations to bloom dynamics. AcI‐C OTUs became more abundant, while acI‐A and acI‐B OTUs declined during the bloom, providing evidence of niche partitioning at the sub‐clade level. Thus, our observations in western Lake Erie support a link between CHABs and disturbances to bacterial community diversity and composition. Additionally, the short recovery of many taxa after the bloom indicates that bacterial communities may exhibit resilience to CHABs.

Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Rose M. Cory; Timothy W. Davis; Gregory J. Dick; Thomas Johengen; Vincent J. Denef; Michelle A. Berry; Sarah E. Page; Susan B. Watson; Kate Yuhas; George W. Kling (Frontiers in Marine Science, 2016)

Billing and Reimbursement for a Bedside Toxicology Service at a Tertiary Care Academic Center During Its First Fiscal Year - Timothy J. Wiegand; Peter W. Crane; Michael Kamali; Marilynn Reif; Rose Wratni; Ronald Montante; Tracey Loveland (Journal of Medical Toxicology, 2015)

A road map for molecular ecology - Rose L. Andrew; Louis Bernatchez; Aurélie Bonin; C. Alex. Buerkle; Bryan C. Carstens; Brent C. Emerson; Dany Garant; Tatiana Giraud; Nolan C. Kane; Sean M. Rogers; Jon Slate; Harry Smith; et al. (Molecular Ecology, 2013)
The discipline of molecular ecology has undergone enormous changes since the journal bearing its name was launched approximately two decades ago. The field has seen great strides in analytical methods development, made groundbreaking discoveries and experienced a revolution in genotyping technology. Here, we provide brief perspectives on the main subdisciplines of molecular ecology, describe key questions and goals, discuss common challenges, predict future research directions and suggest research priorities for the next 20 years.

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Corrigendum - Kimberly J. Gilbert; Rose L. Andrew; Dan G. Bock; Michelle T. Franklin; Nolan C. Kane; Jean‐Sébastien Moore; Brook T. Moyers; Sébastien Renaut; Diana J. Rennison; Thor Veen; Timothy H. Vines (Molecular Ecology, 2013)

Recommendations for utilizing and reporting population genetic analyses: the reproducibility of genetic clustering using the program structure - Kimberly J. Gilbert; Rose L. Andrew; Dan G. Bock; Michelle T. Franklin; Nolan C. Kane; Jean‐Sébastien Moore; Brook T. Moyers; Sébastien Renaut; Diana J. Rennison; Thor Veen; Timothy H. Vines (Molecular Ecology, 2012)
Reproducibility is the benchmark for results and conclusions drawn from scientific studies, but systematic studies on the reproducibility of scientific results are surprisingly rare. Moreover, many modern statistical methods make use of ‘random walk’ model fitting procedures, and these are inherently stochastic in their output. Does the combination of these statistical procedures and current standards of data archiving and method reporting permit the reproduction of the authors' results? To test this, we reanalysed data sets gathered from papers using the software package structure to identify genetically similar clusters of individuals. We find that reproducing structure results can be difficult despite the straightforward requirements of the program. Our results indicate that 30% of analyses were unable to reproduce the same number of population clusters. To improve this, we make recommendations for future use of the software and for reporting structure analyses and results in published works.

One-set resistance training elevates energy expenditure for 72 h similar to three sets - Timothy Heden; Curt Lox; Paul Rose; Steven Reid; Erik P. Kirk (European Journal of Applied Physiology, 2011)

THE SPECIFICITY OF PHENOTYPIC INDUCTION OF MOUSE AND HUMAN STEM CELLS BY SIGNALING COMPLEXES - JIANWU DAI; JANARDAN KUMAR; YAJUN FENG; ROSE ASRICAN; JUNG KIM; TIMOTHY FOFONOFF; VLADIMIR RUSSAKOVSKY; RYAN CHURCHILL; NILOY ROY; EUGENE BELL (In Vitro Cellular & Developmental Biology - Animal, 2002)